2021
DOI: 10.3389/fnins.2021.722894
|View full text |Cite|
|
Sign up to set email alerts
|

rTMS Induces Brain Functional and Structural Alternations in Schizophrenia Patient With Auditory Verbal Hallucination

Abstract: BackgroundLow-frequency transcranial magnetic stimulation (rTMS) over the left temporoparietal cortex reduces the auditory verbal hallucination (AVH) in schizophrenia. However, the underlying neural basis of the rTMS treatment effect for schizophrenia remains not well understood. This study investigates the rTMS induced brain functional and structural alternations and their associations with clinical as well as neurocognitive profiles in schizophrenia patients with AVH.MethodsThirty schizophrenia patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 92 publications
2
20
0
Order By: Relevance
“…The results regarding alterations in clinical symptoms were fully consistent with the previous report ( 32 ). The results also agree with the meta-analysis studies ( 19 , 20 , 46 ) and confirmed the effectiveness of low-frequency rTMS treatment on AVH in schizophrenia with our previous studies ( 33 , 35 37 ). Moreover, rTMS treatment induced beneficial connectivity changes of the seed in the active treatment group, including increased static FC (SFC) with prefrontal regions (e.g., right superior frontal gyrus and right supplementary motor cortex) and decreased SFC with the temporal lobe (e.g., right inferior temporal gyrus and middle temporal gyrus).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results regarding alterations in clinical symptoms were fully consistent with the previous report ( 32 ). The results also agree with the meta-analysis studies ( 19 , 20 , 46 ) and confirmed the effectiveness of low-frequency rTMS treatment on AVH in schizophrenia with our previous studies ( 33 , 35 37 ). Moreover, rTMS treatment induced beneficial connectivity changes of the seed in the active treatment group, including increased static FC (SFC) with prefrontal regions (e.g., right superior frontal gyrus and right supplementary motor cortex) and decreased SFC with the temporal lobe (e.g., right inferior temporal gyrus and middle temporal gyrus).…”
Section: Discussionsupporting
confidence: 92%
“…Unlike our previous studies using case-control paradigm ( 33 , 35 37 ), this study had a single-blind parallel design, only the rTMS administrator rather than researchers or raters knew the conditions to which patients were assigned. Stimulation was performed by a Magstim Rapid System (YIRUDE, Wuhan, China), using a 70 mm figure-of-eight coil.…”
Section: Methodsmentioning
confidence: 99%
“…The second peak (ALE value 0.014; p = 0.00001; z = 4.22) was found in the left IFG (MNI coordinates: X = −36, Y = 10, Z = −16, corresponding to BA 13). Notably, the GingerALE report revealed that none of the three studies showing greater grey matter volume in patients compared to controls ( O’Daly et al, 2007 , Shapleske et al, 2002 , Xie et al, 2021 ) contributed.…”
Section: Resultsmentioning
confidence: 97%
“…In particular, we extracted data for 504 patients with SZ and hallucinations, 524 healthy controls and 74 foci (see Table 2 ). Notably, all these studies reported decreased grey matter in patients compared to controls, and only three studies ( O’Daly et al, 2007 , Shapleske et al, 2002 , Xie et al, 2021 ) further showed greater grey matter volume in patients compared to controls. We carried out the main analysis including all these studies, regardless of the direction (decreased or increased) GMV in AVH-SZ patients with respect to healthy controls.…”
Section: Methodsmentioning
confidence: 99%
“…High-frequency rTMS can regulate the excitability of the cerebral cortex ( Xie et al, 2021 ). In this study, the left dorsolateral prefrontal cortex was targeted by high-frequency stimulation at 10 HZ, which directly enhanced the neural activity in the target-related brain region ( Du et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%